Penerapan osborn’s learning model untuk meningkatkan kemampuan menulis deskripsi peserta didik kelas iv sekolah dasar - Pramita Arum Sari; Slamet Slamet; Joko Daryanto (Didaktika Dwija Indria, 2023)
This research is a CAR (Classroom Action Research) or better known as Classroom Action Research (CAR) which is carried out to find out how the Osborn learning model can be used to improve students' ability to write descriptions. This class action research consisted of cycle III. Each cycle is carried out in 2 x meetings with 2 x 35 minutes in every 1 meeting. This research uses four stages: planning, implementing, observing and reflecting. The completeness criteria set is 70% of all students exceeding KKM 72. The purpose of this research was to determine the improvement in writing description skills by applying the Osborn learning model to grade IV students of SD Negeri Tunggulsari I, Laweyan Subdistrict, Surakarta City. The subjects in this research were the students of Class IV Tunggulsari 1 Elementary School as many as 24 students as well as the fourth grade teachers of SD Negeri Tunggulsari 1. This research was conducted at Tunggulsari I Elementary School in November 2019. Data collection techniques were taken from observation, tests and documentation. This research was conducted at Tunggulsari I Elementary School in November 2019. Data collection techniques were taken from observation, tests and documentation. The results showed that the grades of grade IV students of SD Negeri Tunggulsari I in writing descriptions through the Osborn learning model had achieved KKM completeness 72. The conclusion of this study is to use Osborn's learning model in writing descriptions increased with the percentage of pre-action completeness of 8.33% increased to 33.33% in the first cycle, in the second cycle also increased to 70.83% and again increased to 83.33 % in cycle III. the contribution of research to the world of education is to provide an innovation in terms of learning models that can be applied to overcome one of the problems namely the problem of writing descriptions.